The power of daughters: How physicians' family influences female patients' health - Mette Gørtz; Ida Lykke Kristiansen; Tianyi Wang (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2024)
While physicians are crucial to patient outcomes, what determines physician behavior and decision making remains to be understood. In this paper, we study how physicians' family characteristics influence physicians' behavior and patient health outcomes. Using administrative data from Denmark and the natural experiment of a child's gender, we find that having daughters affects male primary care physicians' practices and the health of their female patients. Specifically, female patients cared for by male physicians with one additional daughter (compared to one additional son) are 5.5% less likely to die from female-specific cancers, including breast and gynecologic cancers. This improvement in outcomes appears to stem from enhanced cancer screening and preventive efforts, leading to earlier detection and more successful prevention. Exploring potential mechanisms, we find that male physicians with more daughters show greater attentiveness to female-specific health guidelines and are more likely to collaborate with women. We also find suggestive evidence from survey data that female patients report higher levels of trust, empathy, and clearer communication with these physicians.
Keywords: I10; I14; J12; 330; Women's Health; Primary Care Physician; Physician Behavior; Practice Style